1966
DOI: 10.2170/jjphysiol.16.462
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Transmembrane Action Potentials and Mechanical Responses of the Venae Cavae and Atria of the Rabbit

Abstract: Since the pulsation of the vena cava was first noticed in the dog by Wallaenus in 1660 (FRANKLIN, 1937), the existence of rhythmical contractions of the venae cavae proximal to the heart in various animals has been reported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 20 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…This is probably because the sinus horns (caval veins) are activated simultaneously with the atria [28,30,[82][83][84][85], thereby masking the sinus activation by the larger P wave (Figure 2). Interestingly, in rabbit, the sinus horn myocardium activates and contracts in synchrony with the atria and has contractility under the regulation of sympathetic and parasympathetic agonists, like atrial and ventricular myocardium (Figure 2d) [86,87]. In mammals, therefore, the sinus myocardium seems to be atrialized in terms of electrical activity and expression of genes, but not in strictly morphological terms.…”
Section: The Sinus Venosus Is Atrialized In Endothermsmentioning
confidence: 99%
“…This is probably because the sinus horns (caval veins) are activated simultaneously with the atria [28,30,[82][83][84][85], thereby masking the sinus activation by the larger P wave (Figure 2). Interestingly, in rabbit, the sinus horn myocardium activates and contracts in synchrony with the atria and has contractility under the regulation of sympathetic and parasympathetic agonists, like atrial and ventricular myocardium (Figure 2d) [86,87]. In mammals, therefore, the sinus myocardium seems to be atrialized in terms of electrical activity and expression of genes, but not in strictly morphological terms.…”
Section: The Sinus Venosus Is Atrialized In Endothermsmentioning
confidence: 99%
“…The difference in the electrical and mechanical activity between the SVC and IVC has been described in both humans and animals. 6,7 Spach et al reported that the excitation extended 2-5 cm into the SVC during SR, but no evidence of electrical activity could be found inside the IVC in either humans or animals. 6 These differences may relate to different developmental processes between the 2 venous systems; the SVC is embryologically derived from the anterior cardinal vein, whereas the terminal segment of the IVC is derived from the right vitelline vein.…”
Section: (A) (B)mentioning
confidence: 99%
“…As to the conduction of the atrial action potentials and contractions to the venae cavae, several papers have already been published (MASHIBA et al, 1963;ITO et al, 1964 andARITA et al, 1966 andARITA, 1966). However, we have as yet very little information on the transmission of impulses from the ventricles to the stem arteries (aorta or pulmonary trunk) as well as their M. ARITA, H. KAWATA AND M. GOTO bulbi, except for a few reports on the amphibia; i. e., a newt or a toad , using a microelectrode (see MAKI and SUZUKI, 1966).…”
Section: Discussionmentioning
confidence: 99%